A energia eólica: um contexto de aprendizagem de física no ensino médio - Monteiro, José Everton Pinheiro (Universidade Federal Rural do Semi-Árido, 2018)
In the actual society ir of fundamental importance an utilizations of sources of electric energy that be replaceable and small mill the environment. One exemple of this kind of energy is the wind. In the work present, realized en extent of Mestrado Nacional Profissional em Ensino de Física (MNPEF), in the polo the Universidade Federal Rural do Semi-Árido (UFERSA), we show one didactic sequent whereupon hearse thematic is conceived how one context of education apprenticeship, contemplating contents of mechanism, how the laws of Newton and the cinematics of taking polias, of thermodynamics, how the process of transference of heat relationals with the origin of winds; of hydro-dynamic to explain the regimes of outflow of the air in the propeller of one aero-generator and your movement of rotation; and of eletro-magnetism to exemplify the conversion, in the aero-generator, of the energy’s kinetics of Ensino Médio Noturno, na Escola Estadual Zenon de Sousa, em Umarizal/RN. The didactic sequence it was planned searching to create situations that stimulated the collective work and the interaction amang teachers and students, sighting one significative apprentices hip. It was utilized many recourses didactics, such as: dialogue classes, conductor text, experimental activities, demonstrative experiments and simulations on computer. How theoretic referential we use the contextualization, complementary such as PCEM, PCN+ and the theory of meaning apprenticeship of David Ausubel, considering the contributions of Marcos Antônio Moreira and Paulo Freire. The sequence is constitute in six meeting executed in twelve classes. The results of evatuations of 45 minutes each. The results of evatuations develop during the your implementations show that yours objectives was reached
Keywords: Contextualização.; Energia eólica.; Física do ensino médio; Contextualization.; Wind energy; Physics of high school; MULTIDISCIPLINAR::ENSINO